Kebijakan Desentralisasi dan Konflik Sosial: (Suatu Studi di Provinsi Maluku Utara) - Julfi Jamil (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2016)
The implementation of decentralization policies often creates social conflict implications related to the struggle for boundaries of autonomous regions with the argument of maintaining regional identity, but not a few conflicts over territory are by design for certain interests. The analysis of this paper uses a grounded theory approach to analyze several findings in the field related to conflicts over territory between West Halmahera Regency and North Halmahera Regency in North Maluku Province with the aim of revealing how the territorial boundary conflict between North Halmahera and West Halamhera districts can occur and how the role of policy actors in designing the conflict.